Controlling the Morphology of Polymers Multiple Scales of Structure and Processing - Mitchell, Geoffrey R.; Tojeira, Ana.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on controlling morphology of different scales for polymers. The authors explain the need for successful control of morphology to yield target macroscopic physical properties in the application of polymers to diverse areas such as engineering materials, nanodielectrics and photonic crystals. The book combines specialized chapters with an introduction to the morphology of polymers and the range of experimental techniques available to evaluate it.
Chapter 1: Scales of Structure in Polymers -- Chapter 2: Evaluating Scales of Structures -- Chapter 3: Crystallisation in Nanocomposites -- Chapter 4: Theoretical Aspects of Polymer Crystallization -- Chapter 5: Controlling Morphology using Low Molar Mass Nucleators -- Chapter 6: Crystallization in Nanoparticles -- Chapter 7: Controlling morphology in 3D Printing -- Chapter 8: Electrically Conductive Nanocomposites -- Chapter 9: Nanodielectrics: The Role of Structure in Determining Electrical Properties -- Chapter 10: Block Copolymers and Photonic Band Gap Materials -- Chapter 11: Relationship Between Molecular Configuration And Stress Induced Phase Transitions -- Chapter 12: Summary.
Keywords: Polymers; Biomaterials; Microtechnology; Microelectromechanical systems; Polymers; Biomaterials; Microsystems and MEMS